Levels of metals, arsenic and phosphorus in sediments from two sectors of a Brazilian Marine Protected Area (Tupinambas Ecological Station) - Hoff, Natasha T.; Figueira, Rubens C. L.; Abessa, Denis Moledo de Souza [UNESP] (Elsevier B.V., 2015)
The Tupinambas Ecological Station (TES) is a Marine Protected Area consisting of two sectors: the Archipelago of Alcatrazes and the Cabras and Palmas islets. This investigation aimed to provide a first diagnosis of the concentrations of metals (Al,Cr,Cu,Fe,Hg,Ni,Pb,Zn), As and P in sediments from the TES. 24 sediment samples were collected in both sectors using a Van Veen grab sampler. Sediment textures and levels of Organic Matter (OM) and CaCO3 were determined, as well as the concentrations of the above-mentioned elements after partial acid digestion. Sediments were predominantly sandy. Higher levels of CaCO3 occurred in the Alcatrazes sector, whereas the OM contents were higher in the islets sector. Metals concentrations were low and associated with fines, while P and As presented a different behavior. The observed concentrations to all studies elements in sediments from the TES were considered as background values. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Marine Protected Area; Metals; Background values; Contamination; Tupinambas Ecological Station; Geochemistry